Kinematics of Soil-Tilling Vibrational Mechanisms (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This scientific article presents a structural analysis of vibrational mechanisms designed for soil tillage. Vibrational mechanisms play a crucial role in enhancing the efficiency of agricultural machinery. They are used for soil loosening, weed elimination, and improving the fertility layer of the soil.